Social activity as an indicator of successful socialization - Yankin, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
Structure and mechanism of social activism of young people as the condition and indicator of successful socialization is revealed in this article.
Keywords: social activism; sense of purpose; creativity; responsibility